2022
DOI: 10.1111/tpj.15713
|View full text |Cite
|
Sign up to set email alerts
|

CBF4/DREB1D represses XERICO to attenuate ABA, osmotic and drought stress responses in Arabidopsis

Abstract: SUMMARY Water stress can severely impact plant growth, productivity and yield. Consequently, plants have evolved various strategies through which they can respond and adapt to their environment. XERICO (XER) is a stress‐responsive RING E3 ubiquitin ligase that modulates abscisic acid (ABA) levels and promotes drought tolerance when overexpressed. To better understand the biological role of XER in stress responses, we characterized a xer‐1 hypomorphic mutant and a CRISPR/Cas9‐induced xer‐2 null mutant in Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…Individual AREB/ABF s were also found targeted by specific TFs. For instance, DcaABI5 was predicted to be specifically targeted by 39 TFs among five AREB/ABF s from D. catenatum , and more detailed analysis showed that DcaABI5 was probably regulated by dehydration-responsive element-binding protein 1C (DREB1C, AT4G25470) and DERB1D (AT5G51990), two proteins involved in cold acclimation and drought tolerance [ 50 , 51 , 52 ]. Overall, the predicted TF regulatory network of the orchid AREB/ABF s implied their potential roles in growth development, stress response, and network associations.…”
Section: Resultsmentioning
confidence: 99%
“…Individual AREB/ABF s were also found targeted by specific TFs. For instance, DcaABI5 was predicted to be specifically targeted by 39 TFs among five AREB/ABF s from D. catenatum , and more detailed analysis showed that DcaABI5 was probably regulated by dehydration-responsive element-binding protein 1C (DREB1C, AT4G25470) and DERB1D (AT5G51990), two proteins involved in cold acclimation and drought tolerance [ 50 , 51 , 52 ]. Overall, the predicted TF regulatory network of the orchid AREB/ABF s implied their potential roles in growth development, stress response, and network associations.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the expression of 246 DEGs with decreased DARs was repressed in MdRAD5B RNAi transgenic plants under dehydration conditions as compared with GL‐3 plants (Figure 4e ). Among these 466 DEGs, homologues of MdRCI2A , MdNF‐YB3 , MdXERICO , MdGBF3 , and MdABF2‐Like are positive regulators of drought tolerance (Kim et al ., 2004 ; Medina et al ., 2005 ; Ramegowda et al ., 2017 ; Sato et al ., 2019 ; Vonapartis et al ., 2022 ). The homologue of MdTSPO increases drought tolerance by enhancing ABA sensitivity (Guillaumot et al ., 2009 ), while the homologue of MdGIM2 decreases drought tolerance by negatively regulating ABA sensitivity (Liu et al ., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…ABA plays a crucial role in plant response to abiotic stresses such as drought and salinity Vonapartis, et al 2022). Under environmental stress conditions, the ABA biosynthesis is enhanced and the elevated ABA content induces seed dormancy, inhibits plant growth, minimizes water loss from transpiration, and induces stress-related gene expression (Bharath, et al 2021; Nakashima and Yamaguchi-Shinozaki 2013).…”
Section: )mentioning
confidence: 99%